(untitled) (Journal of Philosophy Culture and Political Science, 2024)
The World Values Survey (WVS) stands as a foundational tool in the study of global societal values, providing researchers with invaluable data to explore key research areas across diverse socio-political, economic, religious, and cultural contexts. This article presents an overview of the WVS and highlights its significance in shaping our understanding of societal values, attitudes, and beliefs worldwide. Drawing upon examples from Kazakhstan, a rapidly evolving society situated at the crossroads of Asia and Europe, this article illustrates how WVS data have been utilized to investigate a range of pressing social issues. Through a review of research articles by Kazakhstani authors, we explore themes such as public trust, value orientations, youth activities, family dynamics, gender equality, subjective well-being, political stability, and intergenerational value transmission. Additionally, we examine the methodological approaches employed, including literature review, cross-cultural comparison, sociological surveys, and statistical analyses. By elucidating the multifaceted applications of WVS data, this article underscores the WVS’s utility in fostering cross-national collaboration and advancing our understanding of societal dynamics in a rapidly changing world. Key words: World Values Survey, social values, data, trust, opinions.